Interregional Scientific and Practical Conference "Prospects for the Prevention of Infections Managed by Immunoprophylaxis" - E. B. Brusina (Эпидемиология и вакцинопрофилактика, 2018)
Interregional Scientific and Practical Conference "Prospects for the Prevention of Infections Managed by Immunoprophylaxis".